Single‐ and Bi‐component T2* analysis of tendon before and during tensile loading, using UTE sequences. Issue 1 (15th September 2014) - Chang, Eric Y.; Du, Jiang; Iwasaki, Kenyu; Biswas, Reni; Statum, Sheronda; He, Qun; Bae, Won C.; Chung, Christine B.
<x xml:space="preserve">Abstract</x> Background To determine if the application of tensile force alters the single‐ or bi‐component T2* values of human tendons as measured on a clinical MRI scanner with ultrashort echo time (UTE sequences and if single‐ or bi‐component T2* values differ when measured with 2D‐UTE, 3D‐UTE, or 3D‐UTE‐Cones sequences. Methods Ten tendons were imaged before and during the application of tension using various UTE sequences at 3 Tesla. Single and bi‐component T2* analysis was performed pre‐ and posttension and compared with Bonferroni‐corrected paired Wilcoxon tests. Results Range of mean pre‐ and posttension T2* analysis values were: short T2* fraction (78.6–79.7% and 77.3–79.7%, respectively; P = 1.0 for all sequences), long T2* fraction (20.3–21.4% and 20.3–22.7%, respectively; P = 1.0 for all sequences), short T2* (0.9–1.0 ms and 0.9 ms, respectively; P = 1.0 for all sequences), long T2* (19.9–20.4 ms and 21.9–24.0 ms, respectively; P = 0.9 for 2D‐UTE and P = 1.0 for 3D‐UTE and 3D‐UTE‐Cones), and single‐component T2* (2.3–2.5 ms and 2.5–3.2 ms, respectively; P = 1.0 for all sequences). Conclusion No significant difference in single‐ or bi‐component results was found after the application of tension to tendons. Results are similar regardless of UTE sequence used for acquisition. J. Magn. Reson. Imaging 2015;42:114–120. © 2014 Wiley Periodicals, Inc.